Editorial: 2018 (3)2 - Bulent Tarman (Research in Social Sciences and Technology- OpenED Network, 2018)
Dear RESSAT readers and contributors, We are excited to be with you through the May 2018 issue (3/2) of Research in Social Sciences and Technology (RESSAT). We would like to extend our appreciations to all who contributes by submitting or reviewing manuscripts or have been readers of RESSAT. In our second issue of the third year, you will find the articles on various topics of social sciences specifically focusing on education.